Driver and actionable mutations in younger patients with lung cancer - are we searching properly? - Bratova, Monika; Brat, Kristian; Pavlovsky, Zdenek; Sana, Jiri; Slaby, Ondrej (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
AIMS: The authors focused on a group of young lung cancer patients with the aim of better understanding the mechanisms of tumor pathogenesis in these patients and search for potential targetable mutations. METHODS: We collected retrospective data on patients under 40 years diagnosed with lung cancer (NSCLC or small-cell lung cancer) from 2011-2020 at the Department of Respiratory Diseases, University Hospital Brno, Czech Republic. Tumor tissue of these patients was analysed by next-generation sequencing (NGS, a panel of 550 variants in 19 genes). Demographic characteristics, smoking history, histology, molecular-genetic results and clinical stage of the disesase were recorded in all eligible patients from accessible medical databases. RESULTS: Of 17 identified patients in only 8 cases was successful NGS carried out due to lack of sufficient good quality material in the other cases. The most frequently found molecular genetic changes were EGFR, RICTOR and HER2 amplification and MET and FGFR1 amplification. In addition, we found rare pathogenic variants in BRAF and PIK3CA genes. Actionable variants were detected in 75% patients. CONCLUSION: We detected very frequent driver and potentially actionable alterations in young patients with lung cancer. This suggests different mechanisms of carcinogenesis in these patients and indicates that they might benefit more from a specific approach than older lung cancer patients.
Keywords: driver; nádory plic; malobuněčný karcinom plic; nemalobuněčný karcinom plic; mutace; lung cancer; retrospektivní studie; Lung Neoplasms; Humans; Small Cell Lung Carcinoma; Mutation; young patient; lidé; Retrospective Studies; mutation; Carcinoma, Non-Small-Cell Lung